(untitled) (The Review of Diabetic Studies, 2025)
Cardiac arrest remains a leading cause of mortality worldwide, demanding rapid and effective intervention to improve patient survival and neurological outcomes. High-quality cardiopulmonary resuscitation (CPR) forms the foundation of current resuscitation protocols; however, manual chest compressions are often limited by rescuer fatigue, inconsistent depth and rate, and interruptions during critical interventions. To overcome these challenges, mechanical CPR devices such as the LUCAS system have been developed to deliver consistent, In addition to Mandry and Lama systems uninterrupted compressions with the potential to optimize outcomes in both pre-hospital and in-hospital settings. This review synthesizes evidence on CPR protocols and the clinical application of these devices, highlighting their impact on return of spontaneous circulation (ROSC), survival to hospital discharge, and long-term neurological function. While studies demonstrate improvements in compression quality and logistical advantages during transport and advanced procedures, evidence regarding overall survival benefit remains mixed, with cost, training, and complication risks presenting barriers to universal adoption. The integration of mechanical CPR devices into existing protocols represents a promising adjunct to manual resuscitation, particularly in complex or resource-constrained scenarios. Future research should focus on large-scale randomized trials, cost-effectiveness analyses, and technology integration to establish clearer guidelines for device-assisted resuscitation.